2002
DOI: 10.1046/j.1365-2958.2002.03235.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of the Bacillus subtilis structural maintenance of chromosomes (SMC) protein

Abstract: SummaryThe Bacillus subtilis structural maintenance of chromosomes (SMC) protein is a member of a large family of proteins involved in chromosome organization. We found that SMC is a moderately abundant protein ( ~ 1000 dimers per cell). In vivo cross-linking and immunoprecipitation assays revealed that SMC binds to many regions on the chromosome. Visualization of SMC in live cells using a fusion to the green fluorescent protein (GFP) and in fixed cells using immunofluorescence microscopy indicated that a port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 68 publications
8
63
1
Order By: Relevance
“…5 B, iii and iv). The distribution of EptC loci is consistent with the distribution of SMC/MukB protein in other prokaryotes (37).…”
Section: Bioinformatic Analysis Of Eptc Reveals Homology To Smc Protesupporting
confidence: 82%
See 1 more Smart Citation
“…5 B, iii and iv). The distribution of EptC loci is consistent with the distribution of SMC/MukB protein in other prokaryotes (37).…”
Section: Bioinformatic Analysis Of Eptc Reveals Homology To Smc Protesupporting
confidence: 82%
“…This consistent mobility pattern irrespective of oligonucleotide sequences showed that like other SMCs, EptC bound to ssDNA in a dose-dependent but sequenceindependent fashion. Efficient segregation of low-copy plasmids in E. coli is affected by plasmid topology (36), and SMC proteins are well known to alter DNA topology after binding to DNA (7,28,37). A coupled topoisomerase assay was used to examine the effect of EptC on DNA topology (38).…”
Section: Bioinformatic Analysis Of Eptc Reveals Homology To Smc Protementioning
confidence: 99%
“…Heat stable b-galactosidase activity of the bgaB gene from B. stearothermophilus was measured at 62 uC as described elsewhere (Yuan & Wong, 1995;Platt et al, 1972;Sadaie, 1998). Lindow et al (2002) Samples were heated at 68 uC for 5 min before measuring BgaB activity, to inactivate the endogenous b-galactosidase of the lacZ gene of the E. coli in the integrated pMutin plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of MukB has been observed to cause chromosome overcondensation in vivo (Wang et al 2006). Estimates of 1000 bsSMC condensins in B. subtilis (Lindow et al 2002) suggest that there is roughly one bacterial condensin per 10 kb of (replicated) DNA, not terribly different from the eukaryote ratio. SMCs are also found in archaeal species (Hirano 2005), making them a chromosomal protein that can be found in all three domains of life.…”
Section: Universality Of Smc Complexesmentioning
confidence: 99%